1997
DOI: 10.1038/bjc.1997.531
|View full text |Cite
|
Sign up to set email alerts
|

The independence of intrinsic radiosensitivity as a prognostic factor for patient response to radiotherapy of carcinoma of the cervix

Abstract: Summary A study was made of the prognostic value of pretreatment measurements of tumour radiosensitivity (surviving fraction at 2 Gy, SF2) in 128 patients with stage I-Ill carcinomas of the uterine cervix undergoing radiotherapy. The median follow-up time was 47 months. In a univariate analysis stratifying patients according to the median value, radiosensitivity was a significant prognostic factor for overall survival, local control and metastasis-free survival. The 5-year survival rate for tumours with SF2 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
97
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(99 citation statements)
references
References 20 publications
2
97
0
Order By: Relevance
“…In this paper, we present data showing that the ACA can be used as a surrogate measure in the prediction of tumour cell radiosensitivity; the results are supported by two further papers (Dunne et al, 2003;Moneef et al, 2003). Prior to using the ACA, we attempted to measure radiosensitivity in 24 primary bladder tumours using the soft agar clonogenic assay of West et al (1997). However, the success rate was very low (8%), this was attributed to the problem of achieving prolonged cell growth in this assay.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In this paper, we present data showing that the ACA can be used as a surrogate measure in the prediction of tumour cell radiosensitivity; the results are supported by two further papers (Dunne et al, 2003;Moneef et al, 2003). Prior to using the ACA, we attempted to measure radiosensitivity in 24 primary bladder tumours using the soft agar clonogenic assay of West et al (1997). However, the success rate was very low (8%), this was attributed to the problem of achieving prolonged cell growth in this assay.…”
Section: Discussionmentioning
confidence: 69%
“…This conclusion also concurs with seminal studies of Malaise et al (1987) and Deacon et al (1984), updated by Steel (1996) in which they provide considerable evidence that the radiosensitivity of tumours is most reliably measured at 2 Gy. The clinical studies of West and colleagues would support this proposition (West et al, 1997;Bjork-Eriksson et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In carcinoma of the cervix, there are indications pointing to intrinsic radiosensitivity of the tumour as a determinant of outcome following RT (West et al, 1997). The possibility to measure radiosensitivity in the primary tumour would be of great importance when deciding optimal treatment regimen for the individual patient.…”
mentioning
confidence: 99%
“…The test was suggested as a predictive assay. 40 Her work showed that in vitro measurement of tumor cell radiosensitivity is a highly significant prognostic factor for carcinoma of the cervix treated with radiotherapy 41 (Fig. 6).…”
mentioning
confidence: 99%